A inclusão de alunos surdos em uma escola regular do município de Mossoró/RN com auxílio de jogos matemáticos adaptados em língua brasileira de sinais - Nogueira, Silvana da Silva (Universidade Federal Rural do Semi-Árido, 2020)
Thinking about education and inclusion for all has been a challenge for people working in the field of education worldwide, such researchers come together in search of achieving satisfactory results. The dissertation presented here is associated with research that seeks to contribute and build possibilities for the inclusion of deaf people in regular school with the help of a mathematical game adapted in Brazilian Sign Language. With the objective of understanding whether and how adapted mathematical games can contribute to the inclusion of deaf students in a public school in Mossoró / RN, in which eighth and ninth grade mathematics teachers do not communicate in Brazilian Sign Language-LIBRAS. We carried out a qualitative research with a research-intervention methodology that counted on the collaboration of deaf students, listeners and Mathematics teachers from that institution. The investigation started from the theme's predecessor authors and later we developed methodological procedures initiated with observations, interviews, making and applying a game / domino with the mathematical content “notable products” and finally the application of a questionnaire with questions aimed at acceptance and evaluation of the game. In the end, the data indicate effective results for the inclusion process of deaf people in regular school mediated by mathematical games adapted in Brazilian Sign Language. We believe that research can contribute to the teaching / learning of deaf people in regular schools, assist teachers in mathematics classes and collaborate with other researches that follow our line of reasoning
Keywords: Inclusão; Jogos adaptados; Alunos surdos; Ensino de matemática; Inclusionu; Adapted games; Deaf people; Mathematics; MULTIDISCIPLINAR::ENSINO